2021
DOI: 10.1161/circgen.120.003258
|View full text |Cite
|
Sign up to set email alerts
|

Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes

Abstract: Background - Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease (CVD). Type 2 diabetes (T2D) is an independent CVD risk factor that accelerates atherosclerosis. Methods - We performed meta-analyses of genome-wide association studies (GWAS) in up to 2,500 T2D individuals of European ancestry (EA) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 87 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Second, for most of the variants, the direction of association with subclinical atherosclerosis in T2D cases mirrored the direction of association identified with CAD. This echoes the results from the Lu et al 26 study of subclinical atherosclerosis GWAS in T2D only, where they identified 3 significant associations (rs2891168 near CDKN2B-AS1 at 9p21, rs11170820 near FLJ12825 for CAC, and rs7412 near APOE for CIMT), concluding that some CAD loci act through subclinical atherosclerosis in individuals with T2D. Finally, while these associations were only nominally significant, the contributions from the interaction tests were the primary drivers of the nominally significant associations, suggesting that the overall fit of the model was improved by the inclusion of the T2D interaction term.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Second, for most of the variants, the direction of association with subclinical atherosclerosis in T2D cases mirrored the direction of association identified with CAD. This echoes the results from the Lu et al 26 study of subclinical atherosclerosis GWAS in T2D only, where they identified 3 significant associations (rs2891168 near CDKN2B-AS1 at 9p21, rs11170820 near FLJ12825 for CAC, and rs7412 near APOE for CIMT), concluding that some CAD loci act through subclinical atherosclerosis in individuals with T2D. Finally, while these associations were only nominally significant, the contributions from the interaction tests were the primary drivers of the nominally significant associations, suggesting that the overall fit of the model was improved by the inclusion of the T2D interaction term.…”
Section: Discussionsupporting
confidence: 90%
“…All CAD variants, except rs55730499 near LPA , have also previously been identified as associated with CAC in published CAC GWAS. 22,25,26…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CTGF levels were higher in stroke than TIA and are associated with plaque stabilization following stroke [37]. Moreover, GWAS have associated CTGF with coronary artery calcification in type 2 diabetes patients [38]. Upregulation of miR-18a-5p in AIS patients indicates its potential roles in thrombotic or embolic ischemic strokes but needs further investigation.…”
Section: Discussionmentioning
confidence: 99%